PENGEMBANGAN MEDIA QUIET BOOK MONTESSORI DALAM AREA PRACTICAL LIFE - Nurul Syabaniah; Dewi Fitria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aspect of independence is closely related to practical life-based learning. Practical life-based learning was first introduced by Maria Montessori. Maria Montessori explained that one of the characteristics of children ready to face the next life is the independence of each child through practical life activities. Practical life activities are a series of learning activities that are carried out directly to help children become more prepared for the next life. Practical life activities emphasize simple things that children do every day. Some of the reasons why children are not independent and always depend on adults include children's lack of confidence in their ability to complete assigned tasks, which causes children to always expect help from adults. Therefore, the researcher is interested in practicing practical life activities from Maria Montessori, using a learning medium, namely a Quiet Book. The use of appropriate learning media in learning activities is one way to make learning fun. The results of the assessment by the material expert with an overall score of 94.5%. Based on the table according to Widoyoko: 2022 that the results of the material expert assessment are in the “Very Feasible” category, which lies in the range of 83% -100%. The results of the assessment by media experts with an overall score of 98.4%. Based on the table according to Widoyoko: 2022 that the results of the material expert assessment are included in the “very feasible” category, which lies in the range of 83% -100%.